A CASE OF MYELOBLASTIC BLOOD REACTION IN PATIENTS WITH GENERALIZED TUBERCULOSIS AND AIDS - O. N. Kononchuk; T. V. Pyanzova; N. V. Luzina; M. V. Shcherbinin (Klinicist)
The paper describes a case of myeloblastic blood response in a patient with severe generalized tuberculosis in the presence of acquired human immunodeficiency syndrome.